PERUBAHAN EKONOMI DAN POLITIK SURABAYA DI BAWAH HEGEMONI VOC PADA ABAD KE-18 - Andri Setyo Nugroho (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2023)
The establishment of the VOC fortress on the north coast of Java originated from a political contract between Mataram and the Company. Its presence has indirectly led to economic and political changes in Surabaya. The fort, which initially served as a means of defense, shifted to become a center for trade and government. Discussions about the early development of Surabaya mainly stem from the colonial settlements that mushroomed in the 19th century. Even though changes had already emerged when the VOC was based in Surabaya, which started with constructing a fort and infrastructure improvements, subsequently generating economic growth, and encouraging massive political change. The study aims to describe the economic and political changes in Surabaya under VOC hegemony. It used historical research, which sources are taken from archives, maps, and VOC letters from the 18th century. The study results show that the fort has an economic impact, namely increasing trading activities and triggering the formation of Chinese settlements. Political development grew from the fortress, which became the center of Java’s Oosthoek government. Surabaya was chosen as the location for the gezaghebber’s official residence, the seat of government, and the place for the inauguration of the regents in the vicinity.